Gendered beings, gendered discourses: the gendering of race, colonialism and anti-colonial nationalism in three Zimbabwean novels - Mutekwa, Anias (Routledge, 2021)
This article aims to explore the gendering of race, colonialism and anti colonial nationalism in selected novels from the Zimbabwean literary canon with the view of showing how this gendering affected different facets of colonial life and, by implication, post independence life. It relies on the Gramscian concept of hegemony in terms of how it refers to gender, particularly masculinities. The selected texts, A Son of the Soil by Wilson Katiyo, The Grass is Singing by Doris Lessing and Bones by Chenjerai Hove, cover the colonial period from the moment of contact to the early post independence period. The article links the gendered nature of colonialism to the gendered aspects of anti colonial nationalism and shows how the two existed in an oppositional yet ambivalent relationship. This is also manifest in the schizophrenia of the post independence state in modeling itself after its predecessor, its anti colonial rhetoric notwithstanding.